In-vivo EPID dosimetry for IMRT and VMAT based on through-air predicted portal dose algorithm. (August 2018) - Najem, M.A.; Tedder, M.; King, D.; Bernstein, D.; Trouncer, R.; Meehan, C.; Bidmead, A.M.
Highlights: A transit portal dosimetry algorithm was adapted to be used for IMRT and VMAT. A correction factor was introduced in order to maintain the EPID at a fixed SID. The introduced method was validated with the use of several IMRT and VMAT plans. The model's accuracy was tested using several inhomogeneous phantoms. The model's sensitivity was evaluated by introducing deliberate errors into plans. Abstract: We have adapted the methodology of Berry et al. (2012) for Intensity Modulated Radiotherapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT) treatments at a fixed source to imager distance (SID) based on the manufacturer's through-air portal dose image prediction algorithm. In order to fix the SID a correction factor was introduced to account for the change in air gap between patient and imager. Commissioning data, collected with multiple field sizes, solid water thicknesses and air gaps, were acquired at 150 cm SID on the Varian aS1200 EPID. The method was verified using six IMRT and seven VMAT plans on up to three different phantoms. The method's sensitivity and accuracy were investigated by introducing errors. A global 3%/3 mm gamma was used to assess the differences between the predicted and measured portal dose images. The effect of a varying air gap on EPID signal was found to be significant – varying by up to 30% with field size, phantom thickness, and air gap. All IMRT plans passed the 3%/3 mm gamma criteria by more than 95% on the three phantoms. 23 of 24 arcs from the VMAT plans passed the 3%/3 mm gamma criteria by more than 95%. This method was found to be sensitive to a range of potential errors. The presented approach provides fast and accurate in-vivo EPID dosimetry for IMRT and VMAT treatments and can potentially replace many pre-treatment verifications.